2022
DOI: 10.3390/ijerph19138195
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the COVID-19 Pandemic and Hospital Infrastructure Adaptation and Planning—A Scoping Review

Abstract: The SARS-CoV-2 pandemic has put unprecedented pressure on the hospital sector around the world. It has shown the importance of preparing and planning in the future for an outbreak that overwhelms every aspect of a hospital on a rapidly expanding scale. We conducted a scoping review to identify, map, and systemize existing knowledge about the relationships between COVID-19 and hospital infrastructure adaptation and capacity planning worldwide. We searched the Web of Science, Scopus, and PubMed and hand-searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 134 publications
0
26
0
3
Order By: Relevance
“…It should be highlighted that the public response to the pandemic required health system managers to adopt different strategies to expand the installed capacity of care [ 47 ], making the purchase of beds in the private service a reality not only in ES, but worldwide, within which there was the allocation of beds exclusively for COVID-19 patients [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be highlighted that the public response to the pandemic required health system managers to adopt different strategies to expand the installed capacity of care [ 47 ], making the purchase of beds in the private service a reality not only in ES, but worldwide, within which there was the allocation of beds exclusively for COVID-19 patients [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that DHTs allowed them to provide a wide variety of services, from diagnosis to treatment and palliative care, as well as preventative and vaccine drives. In addition, DHTs were utilised to increase the number of non-COVID-19 consultations and referrals to secondary care [9,66] that would have been otherwise dismissed due to COVID-19's early responses, such as cancelling non-urgent treatment, implementing lockdowns, and so on.…”
Section: Dhts To Ensure Continued Phc Delivery During Covid-19mentioning
confidence: 99%
“…The response to the Sars-Cov-2 pandemic, also known as COVID-19 [6], revealed missed opportunities to provide PHC to all. Many health-care services have been postponed in many countries in order to focus on COVID-19 patients [7][8][9]. Other reports show how health systems have faced compounding weaknesses in delivering PHC during COVID-19 [10], including underfunding and postponing some care services.…”
Section: Introductionmentioning
confidence: 99%
“…In different countries, different approaches have been used for treating COVID-19 patients; entire buildings were converted into fully functioning hospitals, full hospitals or only parts of some hospitals were designated for treating COVID patients, or completely new COVID-19 hospitals were built [ 9 , 10 , 11 ]. In Serbia, different places for the healthcare of COVID-19 patients were also used.…”
Section: Introductionmentioning
confidence: 99%